The knowledge of nursing professionals regarding cardiorespiratory arrest in emergency (Research, Society and Development, 2021)
Objective: Discuss the importance of knowledge of nursing professionals facing a situation of cardiac arrest in the emergency department. Methods: This is an integrative literature review, carried out in the Virtual Health Library database, using the descriptors "Knowledge", "Nursing", "Emergency Nursing", "Emergency" and "Heart Arrest" combined with each other through of the Boolean operators "AND" and "OR", covering studies published in the last 5 years (2016-2021), available in full and that answered the guiding question: How the knowledge of nursing professionals implies in their performance in relation to cardiopulmonary arrest in Emergency? Results: Based on the inclusion and exclusion criteria, a final sample of 18 articles was obtained, of which 21.6% corresponding to descriptive study articles, with a predominance of studies published in 2017. Conclusion: It is noticed that constant updates for these professionals are important, contributing to the recognition of the main signs and symptoms of a CPA, performing necessary interventions and qualified maneuvers without interfering with the patient's health. These types of updates can occur through ongoing education projects aimed at the development, autonomy and appreciation of nurses.